Grinding of alumina-reinforced aluminium-based metal matrix composites - 202736 Lau, Chong Yong (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1999